Trainee teachers wellbeing: the association between resilient and mindfulness - Mat Zin, Nur Izzati; Mohamad, Fauzi; Zainudin, Zaida Nor (Human Resources Management Academic Research Society (HRMARS), 2024)
Trainee teachers' wellbeing can be enhanced by mindfulness and resilience, which support them in efficiently managing stress and overcoming obstacles. The purpose of this study is to investigate the wellbeing, resilient, and mindfulness among trainee teachers at one of the Malaysian trainee teacher’s institutes. This study determines the relationship between resilient and mindfulness and the well-being of Malaysian teacher candidates. Additionally, factors that support the well-being of Malaysian trainee teachers have been examined. Using a correlational framework and a quantitative approach, the study counts 239 trainee teachers who were selected at random from the Institute of Teacher Education Malacca. The instruments used for this study include The Flourishing Scale, The Brief Resilience Scale and The Mindful Attention Awareness Scale. The data was analysed descriptively and inferentially using SPSS software. The results show a relationship between trainee teachers' wellbeing, mindfulness and resilient in that particular institute. Moreover, it was found that resilience and mindfulness had an impact on their overall wellbeing. It could be beneficial if this study can help relevant departments, such as the Ministry of Education, create and implement intervention programs to improve resilience and well-being among Malaysian trainee teachers.